Lipid measures are associated with cognitive functioning in multiple sclerosis patients - Lőrincz, Balázs; Motýl, Jiří; Friedová, Lucie; Hrych, Daniel; Kubala Havrdová, Eva; Krásenský, Jan; Urban, Tadeáš; Kober, Tobias; Maréchal, Bénédicte; Vaněčková, Manuela; Horákova, Dana; Vrablik, Michal; et al. (Multiple sclerosis and related disorders, 2024)
BACKGROUND: An association between lipid measures and cognitive decline in patients with multiple sclerosis (MS) has been suggested. OBJECTIVES: This study aimed to investigate relationships between lipid profile and cognitive performance in a large observational cohort of MS patients. MATERIALS AND METHODS: We included 211 patients with 316 available pairs of lipid and cognitive measures performed over follow-up. The time between lipid and cognitive measures did not exceed 90 days. Baseline data were analyzed by non-parametric Spearman rank correlation test. Repeated measures were analyzed using linear mixed models adjusted for sex, age, education level, disease-modifying therapy status, and depression. RESULTS: Baseline analyses showed a correlation between higher low-density lipoprotein cholesterol (LDL-C) and lower Categorical Verbal Learning Test (CVLT) (rho=-0.15; p = 0.04), lower Symbol Digit Modalities Test (SDMT) (rho=-0.16; p = 0.02) and lower Brief Visuospatial Memory Test-Revised (BVMT-R) scores (rho=-0.12; p = 0.04). Higher high-density lipoprotein cholesterol (HDL-C) was negatively correlated with lower SDMT scores (rho=-0.16; p = 0.02) and lower Paced Auditory Serial Addition Test-3 (PASAT-3) scores (rho=-0.24; p = 0.03). Mixed model analyses of repeated measures showed a negative association between higher LDL-C and lower CVLT (B=-0.02; p < 0.001, Cohen´s d = 0.08) and lower BVMT-R (B=-0.01; p = 0.03, Cohen´s d=-0.12). Also, the negative association between HDL-C and PASAT-3 was confirmed in the mixed model analysis (B=-0.18; p = 0.01, Cohen´s d = 0.07). Additional adjustments of the models for disability assessed by Expanded Disability Status Scale or Normalized Brain Volume did not change the results of the models substantially. CONCLUSIONS: Our results suggest a mild negative impact of dyslipidemia on cognitive performance in patients with MS. We propose that dyslipidemia contributes, at least in part, to cognitive decline in MS patients, independent of brain atrophy.
Keywords: dospělí; Female; Cognitive Dysfunction; LDL-cholesterol; Neuropsychological Tests; Adult; Cholesterol, LDL; ženské pohlaví; neuropsychologické testy; lidé; Multiple Sclerosis; LDL; roztroušená skleróza; kognice; Male; HDL; Cholesterol, HDL; HDL-cholesterol; kognitivní dysfunkce; Cognition; lidé středního věku; mužské pohlaví; Multiple sclerosis; Middle Aged; Humans